2023
DOI: 10.56294/dm202340
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Security and Reliability of a Quality Marketing Information System: A Priority Prerequisite for Good Strategic Management of a Successful Entrepreneurial Project

Abstract: Thanks to the security policy of the marketing information system which includes physical, administrative and logical safeguards, organizations are today able to design marketing and sales strategies that enable them to effectively respond and satisfy their customers' needs and expectations in a timely and cost effective manner and this by protecting the relevant information and data circulating in the said information system against any attempt at attack or malicious intrusion which seeks only to harm its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
0
0
1
Order By: Relevance
“…They found a relationship between cyberbullying and reduced selfesteem. A similar finding was established in the work of [44], who identified that cyberbullying is experienced by between 2% and 16% of young people and can lead to school absenteeism, depression, low self-esteem, behavior changes, deterioration in social relationships, and suicide.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…They found a relationship between cyberbullying and reduced selfesteem. A similar finding was established in the work of [44], who identified that cyberbullying is experienced by between 2% and 16% of young people and can lead to school absenteeism, depression, low self-esteem, behavior changes, deterioration in social relationships, and suicide.…”
Section: Introductionsupporting
confidence: 83%
“…The problematic use of social media isn't specifically categorized as a mental disorder. However, this study has identified a growing body of empirical research that highlights symptoms akin to addiction disorders ( [3], [35], [42], [43], [28], [44], [12] and [31]). Precisely, akin to the work of [12,[45][46][47][48][49] and, social media addiction in this paper is considered a subcategory of internet addiction and cyber addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar and different viewpoints were obtained in the mapping against the BMC, and the results provide novelty to advance the understanding and use of the BMC in humanitarian logistics service operations. 25,26 Current trends could have implications for the future of the port business ecosystem, specifically the port of Barcelona, Spain. Therefore, the Business Model Canvas is a framework tool used for the study.…”
Section: Previous Studiesmentioning
confidence: 99%
“…En la actualidad, la sociedad está inmersa en la era de las telecomunicaciones y la información, lo que ha generado una enorme cantidad de datos y conocimientos que pueden ser utilizados para la toma de decisiones (14,18) y el desarrollo económico y social de los países. (19) Esta nueva era ha dado lugar a lo que se conoce como la sociedad del conocimiento, donde el conocimiento es uno de los principales recursos para el desarrollo y la competitividad de los países.…”
Section: Contexto De La Era De Las Telecomunicaciones Y La Sociedad D...unclassified